Report on Agrarian Reform in the United Arab Republic - Land Reforms Division Planning Commission (Planning Commission Government of India, 1966)
The summary of Agrarian Reform in the United Arab Republic examines the post-1952 land reform measures aimed at dismantling feudal landholding structures and promoting equitable access to agricultural land. Central to the reform was the imposition of land ceilings, compulsory acquisition and redistribution of surplus land, and strict regulation of rents and tenancy to ensure security of tenure for cultivators. The establishment of village-level multi-purpose cooperative societies played a pivotal role in implementing reforms, managing land records, providing credit, and facilitating access to agricultural inputs. Complemented by land reclamation initiatives and technical support, these reforms led to notable gains in agricultural productivity and improvements in rural livelihoods. Overall, the U.A.R. experience offers a comprehensive and effective model of agrarian reform with valuable lessons for other developing economies.
Government of India Planning Commission Land Reforms Division
Keywords: Agrarian Reform; United Arab Republic; Land Ceiling Policy; Land Redistribution; Tenancy Regulation; Cooperative Societies; Security of Tenure; Agricultural Credit; Land Reclamation; Rural Development; Small Farmers; Agricultural Productivity